(untitled) (Vietnam Journal of Community Medicine, 2024)
Aims: The study was conducted to determine the glycaemic index of the nutritional cereal YAMMI product. Method: The study followed the method of determining the glycaemic index of food according to the national standard TCVN 10036:2013 (ISO 26642:2010), conducted on 18 healthy adult volunteers. The data were processed and analysis by using Microsoft Excel software and the results were evaluated according to national standards for glycaemic index determination. Results: The glycaemic index of product was 46.0 and the glycaemic load was 7.7. Conclusion: YAMMI, a nutritional cereal product is classified as a lower glycaemic index food and the low glycaemic load food group. The product is used to support a reasonable diet for people with diabetics, obese and those who need to control blood glucose.